Incidence of diseases in germplasms Corchorus olitorius L. and control of fungal pathogens - Nasim, ASM; Hosen, S; Bashar, MA (Dhaka University Journal of Biological Sciences, 2017)
Screening of 40 germplasms and two released varieties of Corchorus olitorius L. was made to determine the source of resistance in jute germplasm against various diseases under condition of natural infection in the field. The germplasm lines were classified on the basis of their per cent disease incidence according to the scale of Mayee and Datar with some modification. There were 12 germplasm lines of Acc. Numbers 1045, 1050, 1060, 1062, 1065, 1143, 1261, 1338, 3711, 3724, 4178, 5009 and variety O‐72, found resistant to jute diseases which can be utilized for developing disease resistant variety. The effects of Bavistin DF, Capvit 50 WP, Dithane M‐45, Hayvit 80 WP, Ridomil Gold MZ 68 WG and Tilt 250 EC were evaluated against Botryodiplodia theobromae, Colletotrichum sp., Fusarium sp. 1, Fusarium sp. 2, Rhizoctonia solani and Sclerotium rolfsii at different concentrations following poisoned food technique. Out of six fungicides, Bavistin, Dithane and Tilt completely inhibited the growth of test pathogens except Sclerotium rolfsii at 500 ppm. Bavistin, Dithane and Tilt also showed promising results against the selected test pathogens at 100, 200 and 400 ppm. The findings of this investigation will be helpful for the plant breeders to select varieties for breeding purposes as well as to control jute pathogens. Dhaka Univ. J. Biol. Sci. 26(2): 189-198, 2017 (July)